The subnasal lip lift. Case studies. (February 2023) - Rosales, H.; Requejo, S.; Suarez, C.; Garcia Guevara, H.
Abstract : Introduction: The subnasal lip lift (SLL) has emerged as a standard procedure for the treatment of an elongated upper lip in conjunction with little upper dental display. SLL using the bullhorn technique, or its modifications allows for shortening of upper lip height, creating a more aesthetically pleasing lip secondary to increased vermilion height and lip pout. Patient selection is critical, considering lip height, vermilion height, alar base width, skin type, upper incisal show, and maxillary height. Precise measurements, controlled excision of the planned resection, and meticulous approximation of skin provide an aesthetic result, while minimizing visible scarring. Methods: The authors conducted a case series study who underwent a SLL procedure without another nasal or lip procedure between January 2017 and December 2021. The outcome variables were lip length, tooth show, vermillion display. Preoperative and postoperative values were compared and analyzed using paired sample t-tests. Results: Overall, 10 female and 2 male patients with an average age of 45 years and a mean follow-up of 15 months were included in the study. SLL resulted in a statistically significant 24.3% reduction in lip length, 33.5% increase in the vermilion show, and a 1.75 mm increase in tooth show (P<.0001). Conclusions: SLL procedure can significantly impact in facial esthetics, specifically by decreasing upper lip height, and improving maxillary teeth display.